Analisis Faktor-Faktor Yang Menyebabkan Rendahnya Pendapatan Asli Dareah Kota Kupang Yang Diperoleh Dari Retribusi Trayek - Alexsander Reynaldi Koli; Stefanus Yulvensius Fransisko Kleruk; Ferdinandus Lobo (Universitas Sains dan Teknologi Komputer, 2023)
In terms of route retribution, the Kupang city government experiences serious problems when collecting route retribution always does not reach the limit or target that has been set. This is a problem that can have an impact on the original opinion of the region (PAD) of Kupang city which will then result in regional development In conducting a study, the author refers to research methods, so that research is more directed and planned. The research method that the author uses is an empirical juridical research method. Based on the results of interviews at the relevant agencies of the Kupang City regional levy management, the revenue target was not achieved due to the passing of the Kupang City regional levy collection. The regional levy revenue target has not been achieved because there are still passes in the payment of regional levy contributions. The ineffective implementation of sanctions is a factor that causes the non-achievement of the regional levy revenue target. Based on the results of an interview with the Head of Regional Revenue Control of the Kupang City Regional Revenue Agency. That the sanctions given have not been effective because there is no coercive basis for the levy obligatory who does not pay or delays the payment of the levy fee. Currently the sanctions given are not effective, this is because of the low level of awareness of mandatory retribution, Kupang City is one of the cities in Indonesia that has quite a lot of public transportation. To regulate and control the number and type of public transportation, the Kupang City government applies a route permit levy. Kupang City is one of the cities in Indonesia that has quite a lot of public transportation. To regulate and control the number and type of public transportation, the Kupang City government applies a route permit levy.